Thyroid Volume in Pregnancy is Associated with Parity, Gestational Age, and Body Mass Index in an Iodine-sufficient Area - Mariana Couto Monteiro; Gabriela Assayag; Ricardo Botler; Anice Bergamin; Flávia Lúcia Conceição; Nathalie Silva de Morais; Roberto Perrota de Seixas; Tatiana Martins Benvenuto Louro Berbara; Annie Schtscherbyna; Carolina Martins Corcino; Débora Ayres Saraiva; Mário Vaisman; et al. (Revista Brasileira de Ginecologia e Obstetrícia, 2023)
Abstract Objective We compared thyroid volume (TV) and presence of nodular goiter (NG) in pregnant vs. non-pregnant women in an iodine-sufficient area. We also evaluated the relationship between gestational age, parity, and TV in the pregnant women group, and determined the 2.5th and 97.5th percentiles of normal TV in pregnancy. Methods This cross-sectional study included 299 healthy women (216 pregnant) without previous thyroid diseases. Thyroid ultrasounds were performed and compared between pregnant and non-pregnant women. The range of normal distribution of TV (2.5th and 97.5th percentiles) in pregnancy was determined after excluding individuals with positive thyroid antibodies, NG, and/or abnormal serum thyrotropin (TSH) or free thyroxine (FT4). Results Thyroid volume was larger among pregnant compared to non-pregnant women (8.6 vs 6.1 cm3; p< 0.001) and was positively correlated with gestational age (rs = 0.221; p= 0.001), body mass index (BMI, rs 0.165; p= 0.002), and FT4 levels (rs 0.118 p= 0.021). Nodular goiter frequency did not differ between the two groups. There was a negative correlation between TV and TSH (rs -0.13; p= 0.014). Thyroid volume was lower among primiparous compared to multiparous patients (7.8 vs 8.9; p< 0.001) and was positively correlated with parity (rs 0.161; p= 0.016). The 2.5th and 97.5th percentiles of TV were 4.23 and 16.47 cm3, respectively. Conclusion Thyroid volume was higher in pregnant compared to non-pregnant women and was positively related to parity, BMI, and gestational age in a normal iodine status population. Pregnancy did not interfere with the development of NG.